STRATEGIC PARTNERSHIP IN ENTROPY CONDITIONS: NEW APPROACHES TO THE DEVELOPMENT OF BUSINESS MODELS OF PRIVATE MEDICAL CLINIC - LAVRENENKO Valentynа; TEPLIUK, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the modern challenges faced by private medical clinics in an entropy-driven environment caused by pandemics, digital transformation, regulatory changes, and socio-economic instability. It demonstrates the decreasing effectiveness of traditional management models, which are being replaced by partnership-based forms of cooperation. The concept of strategic partnership is presented as a tool for risk reduction, innovation potential generation, and stable operation of medical institutions. Particular attention is given to network collaboration models between clinics, the IT sector, insurance companies, and the government. The advantages of transforming business models into open innovation ecosystems and service-oriented platforms are emphasized. The authors propose strategic management approaches based on synergy, digitalization, and adaptability. The practical value of the research lies in its applicability for planning partnership alliances and guiding digital transformation in Ukraine’s private healthcare sector. The study highlights the importance of an interdisciplinary approach to developing effective healthcare management strategies. Engaging stakeholders at various levels enables the formation of multi-format alliances capable of responding swiftly to crisis situations. Particular focus is placed on analyzing the risks and success factors involved in implementing new partnership models. The authors emphasize the need for regulatory support in the transformation of medical business models. The article serves as both a theoretical and practical foundation for designing innovative strategies for private medical business development under conditions of instability. In addition, the research underscores the importance of building long-term institutional alliances that can ensure not only economic efficiency but also the social responsibility of the business. The article also substantiates the relevance of creating medical innovation clusters as the basis of a new healthcare infrastructure. Strategic partnership is shown to facilitate the shift from isolated management practices to open value co-creation platforms. The need to adapt business models to regional disparities and unequal access to digital services is also emphasized. The results presented can be used in future studies on strategic management under entropy conditions.